Impacts of parental health shocks on children's non-cognitive skills - Franz Westermaier; Brant Morefield; Andrea M. Mühlenweg (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We examine how parental health shocks affect children's non-cognitive skills. Based on a German mother-and-child data base, we draw on significant changes in self-reported parental health as an exogenous source of health variation to identify effects on outcomes for children at ages of three and six years. At the age of six, we observe that maternal health shocks in the previous three years have significant negative effects on children's behavioral outcomes. The most serious of these maternal health shocks decrease the observed non-cognitive skills up to half a standard deviation. Paternal health does not robustly affect non-cognitive outcomes.
Keywords: I00; J24; I10; 330; human capital; health; non-cognitive skills